Organizational commitment of police officers in performing their duties under the Chachoengsao provincial police - tanyakul, Teeratorn (Journal of East Asian and ASEAN Studies, 2024)
This research aims to study the level of organizational commitment among police officers working in Chachoengsao Provincial Police. The study aims to compare the organizational commitment of police officers classified by individual factors and to develop recommendations to enhance organizational commitment among police officers working in Chachoengsao Provincial Police. The scope of this study includes: Organizational commitment of police officers working in Chachoengsao Provincial Police. The research findings revealed that the overall level of organizational commitment among police officers working in Chachoengsao Provincial Police was at a moderate level.